Quality and access – Early experience of implementing a virtual stereotactic chart round across a national network. Issue 3 (23rd April 2020) - Fitzgerald, Rhys; Pryor, David; Aland, Trent; Anderson, Lee; Knesl, Marcel; Fong, Andrew; Lunn, Dominic; Oar, Andrew; Jackson, James; Foote, Matthew
Abstract: Introduction: Stereotactic radiation therapy is a highly specialised technique which requires careful and structured implementation. As part of a national stereotactic programme implementation, protocols were developed and a national stereotactic chart round was formed, which strongly recommended attendance and presentation of all cases before treatment. Herein, we describe our experiences launching a national chart round and its importance in a stereotactic programme. Method: Stereotactic chart rounds were held via videoconference between July 2018 and July 2019. Data collected included attendances, patient‐related information including, diagnosis, clinical background, treatment intent, prescribed dose and fractionation and technical approach. Consensus recommendations regarding changes to treatment approaches were also recorded. Results: For the 12 months recorded, there were 1126 attendances, from 144 individual attendees, across 21 locations. In total, 285 cases (237 new cases, and 48 re‐presentations) were presented by 27 radiation oncologists (ROs) from 13 different locations. From the cases presented, 65 changes were recommended from 53 patients (22.3%), including 27 (11.4%) changes to contours, 18 (7.6%) changes to dose prescription/fractionation, 9 (3.8%) changes to plan dosimetry, 1 (0.4%) changes to treatment technique and 10 (4.2%) recommendations for which stereotactic radiation therapy was not advised. A significant inverse relationship was found between frequency of recommended changes and the individual RO's stereotactic case load ( P  < 0.002). Conclusion: The implementation of a national stereotactic chart held via videoconference has ensured national protocol compliance across the network of locations. Furthermore, the chart rounds have allowed the entire multidisciplinary team to be provided with mentorship and guidance. Increasing number of cases presented was associated with lower rates of recommended changes highlighting the impact of experience and the need for continued mentorship.